2010
DOI: 10.1016/j.biocel.2010.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis increases the expression and activity of the transcription factor Forkhead Box O 1 (FOXO1) in skeletal muscle by a glucocorticoid-dependent mechanism

Abstract: Sepsis-induced muscle wasting has severe clinical consequences, including muscle weakness, need for prolonged ventilatory support and stay in the intensive care unit, and delayed ambulation with risk for pulmonary and thromboembolic complications. Understanding molecular mechanisms regulating loss of muscle mass in septic patients therefore has significant clinical implications. FOXO transcription factors have been implicated in muscle wasting, partly reflecting upregulation of the ubiquitin ligases atrogin-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
92
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(101 citation statements)
references
References 57 publications
(149 reference statements)
8
92
1
Order By: Relevance
“…This finding is in agreement with previous reports that suggested that both cecal ligation and puncture (CLP)-and lipopolysaccharide (LPS)-induced sepsis models are associated with increased skeletal muscle FOXO-1 mRNA 43,44 and protein levels. 45 Conversely, we noted that peritonitis was associated with diminished ratio of Akt and FOXO-1 phosphorylated (active)/total protein and that this ratio that appeared to be attenuated with the treatment (Figure 5A and B). These data are consistent with the possibility that the CeO 2 nanoparticle intervention might function to diminish the degree of sepsis-induced muscle breakdown.…”
Section: Ceo 2 Nanoparticle Treatment Improves Protein Degradation/ Smentioning
confidence: 82%
“…This finding is in agreement with previous reports that suggested that both cecal ligation and puncture (CLP)-and lipopolysaccharide (LPS)-induced sepsis models are associated with increased skeletal muscle FOXO-1 mRNA 43,44 and protein levels. 45 Conversely, we noted that peritonitis was associated with diminished ratio of Akt and FOXO-1 phosphorylated (active)/total protein and that this ratio that appeared to be attenuated with the treatment (Figure 5A and B). These data are consistent with the possibility that the CeO 2 nanoparticle intervention might function to diminish the degree of sepsis-induced muscle breakdown.…”
Section: Ceo 2 Nanoparticle Treatment Improves Protein Degradation/ Smentioning
confidence: 82%
“…However, it is well recognized that muscle wasting accompanying sepsis is, in part, due to an elevated rate of protein degradation (49,50,58,59). Data surrounding alterations in muscle protein breakdown in BCATm KO mice are limited and difficult to interpret.…”
Section: Discussionmentioning
confidence: 99%
“…This sepsis-induced muscle atrophy is generally acknowledged to increase morbidity and mortality, as well as slow rehabilitation of this patient population. To date, some therapeutic modalities directed at inhibiting excessive cytokine or glucocorticoid action, or enhancing anabolic hormone availability, have been successfully employed to prevent or minimize muscle wasting in animal models (28,31,41,49,58,59). However, equivocal data have been reported in studies providing metabolic support to critically ill patients using BCAA in general or leucine in particular (5).…”
Section: Perspectives and Significancementioning
confidence: 99%
“…(FOXO)1 and -3a (11,12,21,22,52) regulate muscle-wastingrelated genes in sepsis and other catabolic conditions.…”
mentioning
confidence: 99%